Carotenoid and polyphenol bioaccessibility and cellular uptake from plum and cabbage varieties. (15th April 2016) - Kaulmann, Anouk; André, Christelle M.; Schneider, Yves-Jacques; Hoffmann, Lucien; Bohn, Torsten
Highlights: Variability of plum and cabbage polyphenol/carotenoid bioaccessibility. Mucus layer did not significantly compromise cellular uptake of carotenoids. Higher bioaccessibility/cellular uptake of xanthophylls than carotenes. No difference in bioaccessibility/cellular uptake between Prunus and Brassicaceae. Polyphenols, not carotenoids, were compromised by steaming and boiling of cabbage. Abstract: Plum and cabbage are rich in carotenoids and polyphenols. However, their bioactivity depends on their release and intestinal uptake. Four varieties of Brassicaceae (Duchy, Scots Kale, Kale, Kalorama) and Prunus (Cherry Plum, Plum 620, Ersinger, Italian Plum) were studied; bioaccessibility following in vitro digestion, cellular uptake (Caco-2 vs. co-culture cell model: Caco-2:HT-29-MTX (90:10%) and colonic fermentation were determined for carotenoids/polyphenols; the influence of certain kitchen preparations was likewise studied. Carotenoids were non-significantly influenced by the latter, while for polyphenols, boiling and steaming significantly reduced total phenolics ( p < 0.05). Carotenoid bioaccessibility did not differ significantly between Prunus vs. Brassicaceae varieties, but xanthophyll was higher than carotene bioaccessibility ( p < 0.01). Polyphenol bioaccessibility was low (<10%), possibly compromised by the cream containing test meal. Total carotenoid cellular uptake varied between varieties (0.3–4.1%), being higher for carotenes (4.1%) than for xanthophylls (1.6%, p < 0.01), and were higher for the co-culture cell model compared to Caco-2 cells ( p < 0.01). Total carotenoid recovery in the colonic fraction varied from 4% to 25%. Lower bioaccessibility of carotenes thus appeared to be somewhat counterbalanced by higher cellular uptake. The potential positive role of the mucus layer for cellular uptake and the fate of the colonic digesta deserve further attention in the future.